Coaching : evoking excellence in others - Flaherty, James (Routledge, 2022)
"Now in its fourth edition, the bestselling, seminal book by James Flaherty, Coaching: Evoking Excellence in Others, is an insightful, thought-provoking guide that dissects the art and science of coaching. This fourth edition includes two brand new chapters: the first on finding one's inner guidance and purpose in traversing the world of work, especially in more uncertain working environments; and the second is on the topic of somatic intelligence. As in earlier editions, this foundational book in coaching clearly presents the theories, concepts and models, and then moves on to consider rigorous methods of practice and self-observation in a relationship of mutual trust, respect and freedom of expression. It will probe you to rethink how you relate to your clients and your staff, how you produce long-term excellent performance in yourself and how you can become more effective in helping others to achieve their goals. Coaching, 4th edition is a rich learning resource guide for new and experienced coaches who want to challenge their methods of partnering with clients. It is also an inspiring guide for training managers and leaders, human resource development managers and general managers who want to develop their teams"--